Assessing the Role of Women Entrepreneurs in the Economic Development of Southeastern Nigeria - Jinjiang, Yan; Juliana, Nwokebuife Onyinyechi; Amara, Vandi (Journal of Entrepreneurship, Business and Economics, 2025)
The role of entrepreneurship is important for the economic development of any nation, especially when practiced by women, as it provides employment opportunities for the citizens of the nation. Therefore, this study examines the contribution of women entrepreneurs in the economic development in Enugu and Anambra states, Nigeria. The study employed a non-experimental mixed method design which incorporates both quantitative and qualitative survey. Data were collected from women in various sectors through a structured questionnaire using a stratified random sampling techniques to ensure presentation. The findings from the study revealed most women entrepreneurs aged (26-45) demonstrate strong financial independence and business competency couple with high energy and assurance for monetary freedom, though with limited skills. The findings revealed that access to finance emerged as the strongest predictor (e^(β= 4.5), p< 0.001) of business success while government support positively influenced market access (e^(β= 2.3), p< 0.001). Manufacturing ((β = 12,850, p < 0.001) and retail (β = 9,340, p < 0.001) sectors significantly contributed to job creation and revenue generation. The study was limited to only two states in Nigeria which restrict the generalizability of the findings to other regions. However, strengthening financial access, technical training and government incentives can enhance women entrepreneurial success which can lead to economic growth. The study indicates that empowering women entrepreneurs can foster their financial independence, reduce unemployment and promotes inclusive economic development. Finally, this study provides empirical evidence on the transformative role of women entrepreneurs given key drivers and policy recommendation for business growth. Research Paper Keywords: Women Entrepreneur, Economic growth, Regional development, Southern Nigeria Reference to this paper should be made as follows: Jinjiang, Y., Juliana, N.O., & Amara, V. (2025). Assessing the Role of Women Entrepreneurs in the Economic Development of Southeastern Nigeria. Journal of Entrepreneurship, Business and Economics , 13 (1), 187–235.